(untitled) (Comprehensive Journal of Science, 2026)
This study addresses the issue of political empowerment of Libyan women as a comprehensive civilizational and developmental necessity aimed at the advancement and modernization of society. The paper examines the ongoing tension between constitutional and legislative texts guaranteeing women’s rights and traditional cultural and social norms that hinder their implementation. The study analyzes the various dimensions of empowerment—cognitive, psychological, and economic—emphasizing that financial independence and education are fundamental pillars for women’s self-development and their ability to overcome the "culture of shame" and traditional upbringing. The findings reveal the dominance of a patriarchal mindset within official political structures, necessitating the adoption of national strategies to enhance women’s presence in decision-making positions and activate the role of civil society organizations. The study concludes by stressing the need to modernize societal values ​​through media and educational institutions to create a democratic environment that supports women’s effective political participation, free from marginalization, thus ensuring a balance between the demands of modernity and the cultural roots of Libyan society.